Анализ нелинейности амплитудно-частотной характеристики существующих микрофонов - Тарута, В. И.; Прокопюк, П. Р. (My University, 2018)
Choosing the right microphone is one of the most important decisions on the way to quality recording. The microphone is the connecting link between the acoustic sound created by this or that instrument or voice, and the way this sound is recorded. The amplitude-frequency characteristic describes the deviation of the signal amplitude from the amplitude of the original at a particular frequency within a certain range. These deviations occur due to various factors, among which are the features of the membrane design, its material and weight, as well as design solutions for the implementation of internal circuits and microphone blocks.
Keywords: микрофон; запись